Development of a Digital RT-PCR Method for Absolute Quantification of Bluetongue Virus in Field Samples - Rocchigiani, Angela M.; Tilocca, Maria G.; Portanti, Ottavio; Vodret, Bruna; Bechere, Roberto; Di Domenico, Marco; Savini, Giovanni; Lorusso, Alessio; Puggioni, Giantonella (Frontiers in Veterinary Science, 2020)
Bluetongue (BT) a major OIE-listed disease of wild and domestic ruminants caused by several serotypes of Bluetongue virus, a virus with a segmented dsRNA genome belonging to the family Reoviridae, genus Orbivirus. BTV is transmitted through the bites of Culicoides midges. The aim of this study was to develop a new method for quantification of BTV Seg-10 by droplet digital RT-PCR (RTdd-PCR), using nucleic acids purified from complex matrices such as blood, tissues and midges, that notoriously contain strong PCR inhibitors. First, RTdd-PCR was optimized by using RNAs purified from serially 10-fold dilutions of a BTV-1 isolate (105,43TCID50/mL up to 10-0,57 TCID50/mL) and from the same dilutions spiked into fresh ovine EDTA-blood and spleen homogenate. The method showed a good degree of linearity (R2?0.995). The limit of detection (LoD) and the limit of quantification (LoQ) established were 10-0.67TCID50/mL (0.72 copies/µl) and 100.03TCID50/mL (3.05copies/µl) of BTV-1, respectively. Second, the newly developed test was compared, using the same set of biological samples, to the RT-qPCR detecting Seg-10 assay widely used for the molecular diagnosis of BTV from field samples. Results showed a difference mean of 0.30 log between the two assays with these samples (p-value<0.05). Anyway, the analysis of correlation demonstrated that both assays provided similar measurements with a very close agreement between the systems.